The global course of the information revolution recurring themes and regional variations / Richard O. Hundley [and others] - Hundley, Richard O. (National Defense Research Institute, Rand, 2003)
Advances in information technology are heavily influencing ways in which business, society, and government work and function around the globe, bringing many changes in a process commonly termed the "information revolution." Document portrays the state of the information revolution today--in its technological, business and financial, governmental, and social and cultural dimensions--and how it will likely progress in the next 10 to 15 years. Focuses separately on different regions of the world, including North America, Europe, the Asia-Pacific region, Latin America, the Middle East and North Africa, and Sub-Saharan Africa. Also looks in depth at recurring themes in information technology's impact around the world, including, for example, its influence on business models and its interrelationship with social and cultural value systems.